Governance of Informal Food Vendors in African Cities - Resnick, Danielle (2017)
LAUNCH: 2017 Global Food Policy Report MAR 23, 2017 - 12:15 PM TO 01:45 PM EDT Danielle Resnick, Senior Research Fellow, Development Strategies and Governance Division, IFPRI